The examination of corneal curve in refractive anomaly - A. Soemarsono A. Soemarsono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1984)
The corneal curvature is an important medium refractum because it gives the strongest refraction.The measurement of corneal curve has a direct connection with refraction. The measurements of the emmetropic, myopic, hypermetropic and astigmatic cornea have been presented. The mean of the emmetropic cornea! curve was 42.796 D, that of the myopic was 44.275 D. Statistically, there was significant difference between those of emmetropic and myopic cornea.The mean curve of hypermetropic eyes was 42.843 D. However, statistically there was no difference between the emmetropic and hypermetropic corneal curve.In astigmatism there were always differences between the vertical and horizontal curves. Key Words: corneal curve - emmetropy - myopy - hypermetropy - astigmatism